Irisin ameliorates male sexual dysfunction in paroxetine-treated male rats - Canpolat, Sinan; Ulker, Nazife; Yardimci, Ahmet; Tancan, Emre; Sahin, Elif; Yaman, Serap Ozer; Ozcan, Mete (Pergamon-Elsevier Science Ltd, 2022)
Sexual dysfunction is a common clinical condition due to different causes including the use of selective serotonin reuptake inhibitors (SSRI). Especially, SSRI paroxetine is known to cause numerous types of sexual dysfunction in men. There is growing interest in exercise as a non-pharmacological approach for the treatment of SSRI-induced sexual dysfunction. With these in mind, we investigated the effects of irisin, which is a recently detected exercise-linked hormone, on paroxetine-induced sexual dysfunction in male rats. Our findings showed that circulating irisin levels were lower in paroxetine-induced sexual dysfunction in male rats (20 mg/kg/day for 8 weeks by oral gavage than in vehicle-treated rats). In addition, results from sexual behavioral tests revealed that subcutaneous irisin perfusion (100 ng/kg/day via mini-osmotic pumps for 28 days) ameliorated sexual motivation and copulatory performance in sexually impaired male rats treated with paroxetine. The significantly reduced serum testosterone levels and alpha 1-adrenoceptors (ADRA1A) and tyrosine hydroxylase gene (TH) expression levels in the nucleus accumbens (NAc) in paroxetine-induced sexually dysfunctioning male rats were markedly increased following irisin exposure. Similarly, the expression levels of ADRA1A and TH in the medial preoptic area (mPOA) significantly increased in male rats co-administered with paroxetine and irisin compared to the vehicle-treated male rats. These results demonstrate that irisin may be a therapeutic modality that mimics/supports the bene-ficial effects of exercise for improving SSRI-associated sexual dysfunction in men through increase in serum testosterone levels and increased expression of alpha 1-adrenoceptors and TH in the NAc and mPOA associated with sexual motivation and copulatory behaviors.
Keywords: Hormones; Irisin; Medial preoptic area; Nucleus accumbens; Paroxetine; Sexual dysfunction